DIFFERENTIATION OF POWERS OF STATE AUTHORITIES OF THE RUSSIAN FEDERATION AND LOCAL GOVERNMENTS IN THE CONTEXT OF SUSTAINABLE TOURISM - Chebotareva, I.A. (Scientific Journal of Pedagogy and Economics, 2020)
This article provides the first legal justification for the thesis that involvement of regional authorities in development of the tourism industry is an international obligation of the Russian Federation in the field of sustainable tourism development. The key to its effective implementation should be a differentiated legal regulation of the powers of state bodies at various levels. In the study of the powers of the Russian Federation and its subjects in the field of sustainable tourism development, analysis and synthesis methods were used, as well as a combination of comparative and formal legal methods. The study revealed legislative separation of competencies and powers between the Russian Federation and its entities in the tourism sector does not fully comply with international obligations of the state. The concentration of “tourist” powers in the hands of the federal authorities will not allow achieving the Sustainable Development Goals in the tourism sector of the economy, and also significantly reduces effectiveness of state tourism policy.